Distinct features of multivesicular body‐lysosome fusion revealed by a new cell‐free content‐mixing assay - Karim, Mahmoud Abdul; Samyn, Dieter Ronny; Mattie, Sevan; Brett, Christopher Leonard (Traffic (Copenhagen, Denmark), 2018)
When marked for degradation, surface receptor and transporter proteins are internalized and delivered to endosomes where they are packaged into intralumenal vesicles (ILVs). Many rounds of ILV formation create multivesicular bodies (MVBs) that fuse with lysosomes exposing ILVs to hydrolases for catabolism. Despite being critical for protein degradation, the molecular underpinnings of MVB‐lysosome fusion remain unclear, although machinery underlying other lysosome fusion events is implicated. But how then is specificity conferred? And how is MVB maturation and fusion coordinated for efficient protein degradation? To address these questions, we developed a cell‐free MVB‐lysosome fusion assay using Saccharomyces cerevisiae as a model. After confirming that the Rab7 ortholog Ypt7 and the multisubunit tethering complex HOPS (homotypic fusion and vacuole protein sorting complex) are required, we found that the Qa‐SNARE Pep12 distinguishes this event from homotypic lysosome fusion. Mutations that impair MVB maturation block fusion by preventing Ypt7 activation, confirming that a Rab‐cascade mechanism harmonizes MVB maturation with lysosome fusion. Endocytosis culminates with multivesicular bodies (MVBs) fusing with lysosomes. But the molecular underpinnings of this event remain unclear. Here, using Saccharomyces cerevisiae as a model, Karim et al employ a new in vitro assay to show that MVB‐lysosome fusion is driven by endosomal sorting complexes required for transport (ESCRT)‐dependent Rab‐GTPase activation and the syntaxin ortholog Pep12, distinguishing it from other lysosome membrane fusion events.